2004
DOI: 10.1016/j.jtcvs.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Left internal thoracic artery−radial artery composite grafts as the technique of choice for myocardial revascularization in elderly patients: a prospective randomized evaluation

Abstract: Left internal thoracic artery-radial artery composite grafts proved to be a safe procedure in elderly patients. It improved the clinical outcome, providing a significantly higher graft patency rate and a lower incidence of late cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 12 publications
3
44
0
Order By: Relevance
“…In our study, we avoided the use of the RA in over 70-year-old patients, nevertheless recent studies showed better results of the RA compared to the SV in this group of patients, with a lower incidence of neurologic complications and similar mortality rates [25].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our study, we avoided the use of the RA in over 70-year-old patients, nevertheless recent studies showed better results of the RA compared to the SV in this group of patients, with a lower incidence of neurologic complications and similar mortality rates [25].…”
Section: Discussionmentioning
confidence: 87%
“…Vasospasms are an important complication of the RA and are described by some authors [13,15,25] and are highlighted as the main cause of graft failure [23]. Coronary lesions of less than 75% were related to the presence of competition of flow in the RA, leading to spasms and occlusion of the graft [7,13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Muneretto et al [30], also in a publication from 2004, compared the patency of RA and SV grafts over 12 months. The angiographic results of 152 patents distributed into two groups were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Category D were excluded from this systematic review. Two studies were classified in Category A (Dessai et al, 2004; Buxton et al, 2003) [29,30] and one study was classified as Category B (Muneretto et al, 2004) [31].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…Muneretto, et al 42) published the results of a prospective trial enrolling 160 patients older than 70 years randomized to the use of RA or SVG as a second conduit. The RA group reported better results in terms of angiographic patency and lower recurrence of angina after a mean follow-up of 16 months.…”
Section: Radial Artery In the Elderlymentioning
confidence: 99%